Teknologi informasi dan komunikasi dalam UMKM: Tinjauan sistematis literatur - Kristanto, Eri; Anggraeni, Rahayu (ICON Publisher, 2025)
The application of information and communication technology (ICT) in Micro, Small, and Medium Enterprises (MSMEs) continues to increase gradually. However, the implementation of ICT in MSMEs is hampered by constraints, such as limited financial resources and ICT knowledge. This study aims to identify and analyze ICT adoption in MSMEs. Additionally, this study aims to provide recommendations on the most effective methods for optimizing ICT utilization in this context. This review was conducted using a sample of four publications that have been published and are available in nationally accredited Sinta 2 journals in the Binus Business Review. The selection process focused on works published between 2015 and 2024. The PRISMA form was used to explain the selection and acceptance procedures for relevant publications comprehensively. The authors' final argument in this article is that, despite extensive research in the field of ICT, there is a need to adapt strategies and policies that can support MSMEs in Indonesia.